Best Answer

Q: How do you solve 4x2 - 4x plus 2 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4x2+50x = 0 4x(x+12.5) = 0 x = 0 or x = -12.5

4x2 - 13 x + 3 = 0 (4x - 1)(x - 3) = 0 x = 3, 1/4

4x2+49x+90 = (4x+9)(x+10) when factored

-((4x + 1)(x - 1))

(4x - 32)(x - 2) so x = 2 or 8

Related questions

4x2 = -12x, divide both sides by 4x: x = -3

4x2+50x = 0 4x(x+12.5) = 0 x = 0 or x = -12.5

4x2 - 13 x + 3 = 0 (4x - 1)(x - 3) = 0 x = 3, 1/4

4x2+49x+90 = (4x+9)(x+10) when factored

-((4x + 1)(x - 1))

(4x - 32)(x - 2) so x = 2 or 8

4x2-4x+1 = (2x-1)(2x-1)

4x2=8 8+22=30 You get 30 it really is simple

-4x2 + 5x + 6 = 0 Multiply through by -1: 4x2 - 5x - 6 = 0 (I prefer the leading coefficient to be >0) 4x2 - 8x + 3x - 6 = 0 4x(x - 2) + 3(x - 2) = 0 (x - 2)(4x + 3) = 0 So x - 2 = 0 or 4x + 3 = 0 ie x = 2 or x = -3/4

The answer is: x = -5/2 and x = 7/2

ANSWER: -4X2 -8X-4x (x+2)= (-4x * x) + (-4x*2)= -4X2 -8X

It is: -4x^2 +11x -6 equals (-4x+3)(x-2) when factored